Advanced Coatings for Buildings - Flores-Colen, Inês; Maury-Ramirez, Anibal C.; Kanematsu, Hideyuki (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Based on five Special Issues in Coatings, this e-book contains a series of 15 articles demonstrating actual perspectives and new trends in advanced coatings in buildings. Innovative materials and multiperformance solutions provide a basis, contributing also to the better protection of buildings' surfaces during the service life, and the users' wellbeing.